The median raphe nucleus in anxiety revisited - Andrade, Telma Gonçalves Carneiro Spera de [UNESP]; Zangrossi, Helio; Graeff, Frederico G. (Sage Publications Ltd, 2013)
Although the role of the median raphe nucleus (MRN) in the regulation of anxiety has received less attention than that of the dorsal raphe nucleus (DRN) there is substantial evidence supporting this function. Reported results with different animal models of anxiety in rats show that whereas inactivation of serotonergic neurons in the MRN causes anxiolysis, the stimulation of the same neurons is anxiogenic. In particular, studies using the elevated T-maze comparing serotonergic interventions in the MRN and in the DRN indicate that the former affect only the inhibitory avoidance task, which has been related to generalized anxiety. In contrast, similar operations in the DRN change both the inhibitory avoidance and the one-way escape task, the latter being representative of panic disorder. Simultaneous injections of 5-HT-acting drugs in the MRN and in the dorsal hippocampus (DH) suggest that the MRN-DH pathway mediates the regulatory function of the MRN in anxiety. Overall, the results discussed in this review point to a relevant role of the MRN in the regulation of anxiety, but not panic, through the 5-HT pathway that innervates the DH.
Keywords: Median raphe nucleus; dorsal raphe nucleus; hippocampus; serotonin; anxiety and panic